2000
DOI: 10.1007/s11663-000-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Redox equilibria and kinetics of gas-slag reactions

Abstract: Measurements of redox equilibria involving a number of transition metals (Fe, Mn, Ti, and V) are summarized and discussed with respect to the effects of oxygen activity and chemistry of the melts on the oxidation state of the transition metal oxide. Recently measured data on kinetics of CO-CO 2 on surfaces of calcium silicate-based slags containing 1 to 68 wt pct FeO x or 18 to 38 wt pct MnO x are presented and discussed in terms of the limiting steps and the dependence of the limiting step on concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…CaO-FeOx metal initial 1% As slag initial 1% As FeOx-SiO 2 metal initial 1% As This outcome was supported by Michal and Schuhmann's [20] finding that the Fe 3+ /Fe 2+ ratio increases with a decrease in SiO 2 in the slag. It is worth noting that as a basic oxide, MgO tends to increase the Fe 3+ / Fe 2+ ratio in slags [21,22] ; thus, the measured higher Fe 3+ /Fe 2+ ratios in the MgO saturated iron silicate slags is partly caused by MgO. The measured distribution ratio L S=C As between the calcium ferrite slags and the iron silicate slags and metal are plotted against the oxygen partial pressure in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…CaO-FeOx metal initial 1% As slag initial 1% As FeOx-SiO 2 metal initial 1% As This outcome was supported by Michal and Schuhmann's [20] finding that the Fe 3+ /Fe 2+ ratio increases with a decrease in SiO 2 in the slag. It is worth noting that as a basic oxide, MgO tends to increase the Fe 3+ / Fe 2+ ratio in slags [21,22] ; thus, the measured higher Fe 3+ /Fe 2+ ratios in the MgO saturated iron silicate slags is partly caused by MgO. The measured distribution ratio L S=C As between the calcium ferrite slags and the iron silicate slags and metal are plotted against the oxygen partial pressure in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Therefore, direct measurements of the FeO activity of CaO-SiO 2 -Al 2 O 3 -IN bath smelting, the rate of reduction is proportional to MgO sat -Fe t O slags, equilibrated with liquid iron, are the FeO content of the slag in the smelter. The sulfur content required.…”
Section: Introductionmentioning
confidence: 99%
“…This is thought to be due to relatively low concentrations of Fe 21 in these samples, which contain 5 wt pct FeO x and were pre-equilibrated in air. Based on these data and a review of published data on redox equilibria in basic slags under oxidizing atmosphere, [18] the authors concluded that the predominate oxidation state of iron in these slags is Fe 31 with very low levels of Fe 21 . Mn 31 and Mn 41 are not very stable at high temperatures, and according to the published redox equilibria data, [19] the Mn 31 /Mn 21 should be about 0.2 in the slags studied at about 1500°C in air.…”
Section: Resultsmentioning
confidence: 99%